Avidin-biotin ELISA for measurement of prothrombin in human plasma - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
In this study, IgG was partially purified from rabbit antisera against human normal prothrombin. The presence of antibodies against prothrombin was shown by Ouchterlony's double immunodiffusion method. This IgC was adsorbed to microwells and an enzyme-linked immunosorbent assay (ELISA) method was developed by using biotinylated prothrombin. We used alkaline phosphatase as the labeling enzyme. Plasma prothrombin concentrations in 30 healthy individuals and 15 patients with liver cirrhosis were measured using this ELISA method. Prothrombin levels of the cirrhotic patients (61 +/- 36 mug/ml) were significantly lower than those of the control values (117 +/- 43 mug/ml) (P < .001). In addition to the ELISA method in the same samples, we assayed prothrombin levels by nephelometry and prothrombin activities using staphylocoagulase and chromogenic substrate. With nephelometry, in healthy individuals, a mean value of 104 +/- 17 mug/ml and, in cirrhotic patients, a mean value of 51 +/- 26 mug/ml of prothrombin levels were detected. The prothrombin activities were 10532 +/- 2429 and 2433 +/- 330 U/l, respectively. In both methods, the prothrombin values of cirrhotic patients were also significantly lower than those of the healthy individuals (P<.001). The correlation coefficient between ELISA and nephelometry was r = .90, P <less than> .01, and between ELISA and the amidolytic assay was v = .69, P < .01. Prothrombin times (PT) of cirrhotic patients (18.5 +/- 2.3 s) were significantly longer and albumin (2.3 +/- 0.5 g/dl) levels were significantly lower than those of normal values (P<.001). PT were negatively correlated with prothrombin levels assayed by ELISA (r = -.59, P <less than> .01). This enzyme immunoassay technique can be used to measure prothrombin levels in plasma. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: ELISA; avidin-biotin; nephelometry; prothrombin; antibody preparation; IgG purification; liver disease; GAMMA-CARBOXY PROTHROMBIN; HEPATOCELLULAR-CARCINOMA; LIVER-DISEASE; ABNORMAL PROTHROMBIN; ALPHA-FETOPROTEIN; MARKER; CARBOXYPROTHROMBIN; IMMUNOASSAYS; DEFICIENCY